Analisis Mutu Pelayanan Instalasi Farmasi pada RSUD Cilacap dan RS PKU Muhammadiyah Karanganyar - SAMPURNO SAMPURNO; AWIK ABRAR AJI; INDRI KUSUMA DEWI (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
An investigation on the quality service at the Pharmacy Department of Cilacap Local Government Hospital (CLGH) and Mohammadiyah Hospital in Karanganyar (MHK) which covered five service dimensions, i.e. reliability, responsiveness, assurance, empathy and tangible factors, has been conducted, The quality of services was analyzes by using the SERVQUAL gap model. The study Was a non-experimental descriptive research. The data were collected using purposive sampling with questionnaires as the research tools. The results showed that in the pharmacy departments, of both CLGH and MHK), the above-mentioned pharmacy service dimensions observed performed below customer expectations. The highest gap score in CLGH is on responsiveness followed by tangible factors, reliability, empathy and assurance. The biggest gap score in MHK is on tangible factors, followed by empathy, assurance, responsiveness and reliability, Loyalty of customer to pharmacy department of CLGH for regular patient is around 50,6%, MHK 39,5%, neutral customer 35,1%, and non-loyal customer 25,4%. The results indicated that both hospitals need to strengthen quality services of their pharmacy departments, particularly on service dimensions which have high score gap.